Epigenetic Targets in Synovial Sarcoma: A Mini-Review - Hale, Ryland; Sandakly, Sami; Shipley, Janet; Walters, Zoë (Frontiers in Oncology, 2019)
Synovial Sarcomas (SS) are a type of Soft Tissue Sarcoma (STS) and represent 8-10% of all STS cases. Although SS can arise at any age, it typically affects younger individuals aged 15-35 and is therefore part of both paediatric and adult clinical practices. SS occurs primarily in the limbs, often near joints, but can present anywhere. It is characterised by the recurrent pathognomonic chromosomal translocation t(X;18)(p11.2;q11.2) that most frequently fuse SSX1 or SSX2 genes with SS18.This leads to the expression of a SS18-SSX fusion protein, which causes disturbances in several interacting multiprotein complexes. Furthermore, this promotes widespread epigenetic rewiring, leading to aberrant gene expression that drives the pathogenesis of SS. Good prognoses are characterised predominantly by small tumour size and young patient age. Whereas, high tumour grade and an increased genomic complexity of the tumour constitute poor prognostic factors. The current therapeutic strategy relies on chemotherapy and radiotherapy, the latter of which can lead to chronic side effects for paediatric patients. In this mini-review, we focus on the known roles of the mammalian ortholog to the yeast SWItch/Sucrose Non-Fermentable (SWI/SNF) complex, also known as the BAF complex and the Polycomb Repressive Complex 1 and 2 (PRC1 and PRC2) as main effectors of the SS18-SSX mediated epigenome modifications. Based on the fundamental roles of these complexes in SS biology, we present existing biological rationale for potential therapeutic targets and treatment strategies.